DEVELOPMENT AND PREDICTION OF RISK FACTORS FOR A MULTI-LEVEL PROGRAM FOR THE PREVENTION OF CHILDHOOD DISABILITY - D. A. Kasimova (Web of Journals Publishing, 2024)
Children's disability is a major problem today. Hundreds of thousands of disabled children need attention and support of society, social, medical and other assistance. The relevance of this issue indicates the quantitative growth of disability in childhood and adverse trends in its structure.
Keywords: Child disability, risk factors for childhood disability, health care for children with disabilities.